Analysis of Models of Doxorubicin-Induced Cardiomyopathy in Rats and Mice. A Modern View From the Perspective of the Pathophysiologist and the Clinician - Podyacheva, Ekaterina Yu; Kushnareva, Ekaterina A.; Karpov, Andrei A.; Toropova, Yana G. (Frontiers in Pharmacology, 2021)
Today the pharmacological possibilities of treating cancer are expanding and as a result, life expectancy is increasing against the background of chemotherapy and supportive treatment. In the conditions of successful antitumor treatment, complications associated with its toxic effect on healthy tissues and organs began to come to the fore. Anthracycline cardiomyopathy was the first serious cardiovascular complication to draw the attention of oncologists and cardiologists around the world. Anthracycline drugs such as doxorubicin, epirubicin, idarubicin are still widely used in oncological practice to treat a wide range of solid and hematological malignancies. Doxorubicin-induced cardiomyopathy is closely associated with an increase in oxidative stress, as evidenced by reactive oxygen species (ROS) induced damage such as lipid peroxidation, and decreased levels of antioxidants. Myofibrillar destruction and dysregulation of intracellular calcium are also important mechanisms, usually associated with doxorubicin-induced cardiotoxicity. Despite the abundance of data on various mechanisms involved in the implementation of doxorubicin-induced cardiotoxicity, a final understanding of the mechanism of the development of doxorubicin cardiomyopathy has not yet been formed. It poses the most significant challenges to the development of new methods of prevention and treatment, as well as to the unambiguous choice of a specific treatment regimen using the existing pharmacological tools. In order to resolve these issues new models that could reflect the development of the chemotherapy drugs effects are needed. In this review we have summarized and analyzed information on the main existing models of doxorubicin cardiomyopathy using small laboratory animals. In addition, this paper discusses further areas of research devoted to the development and validation of new improved models of doxorubicin cardiomyopathy suitable both for studying the mechanisms of its implementation and for the preclinical drugs effectiveness assessment.